Reconceptualizing Educational Assessment and Evaluation: Toward an Integrated Conceptual Framework in the Digital Era - Mohammad Futuh Muafi; Moh. Sahlan; Muhammad Nur Afandi; Muhammad Darul Ulum (PT. Hasba Edukasi Mandiri, 2026)
This research aims to reconceptualize educational assessment and evaluation by developing an integrated framework responsive to the complexities of the digital era. Employing a conceptual methodology based on theory synthesis and narrative literature review, this study integrates classical assessment theories with contemporary perspectives from learning analytics and artificial intelligence. The resulting framework positions assessment as a continuous, adaptive, and systemic process embedded within learning activities. It unifies Assessment for Learning, Assessment as Learning, and Assessment of Learning into a single continuum, while connecting pedagogical dimensions, assessment architecture, and digital technological ecosystems. The findings indicate that the integration of digital technologies enables real-time data processing and personalized feedback, yet must remain grounded in strong pedagogical and ethical principles. This research provides a holistic theoretical foundation for developing more adaptive and learner-centered assessment systems in the digital era.